ANALISIS KONTRIBUSI SEKTOR PERTANIAN DI KABUPATEN SINTANG - Iskandar B01109096, Hipius Joni (Jurnal Curvanomic, 2015)
This study is titled "Analysis of Agricultural Sector Contribution of sub district Sintang" with the purpose is to determine the contribution of the agricultural sector, sub-sector seed, changes in the agricultural sector and the projected development of the agricultural sector in sub district of Sintang. This study used a descriptive method, to identify the sub-sector seed used Location Quotient (LQ), to determine changes in the agricultural sector use Shift Share Analysis (SSA) and to determine the projected development of the sub-sectors of seed used method of extrapolation (trend). The results showed that the sub-sector Contributions of Plant Foodstuffs with an average of 25.88%, the contribution of the plantation sub-sector average of 52.28%, the contribution Livestock sub-sector average of 11.97%, the contribution of forestry sub-sector an average of 7.52%, and fisheries sub-sector average of 2.34%. Sub-sectors that have LQ value above the one that is in the Agricultural Sector Sub Sub Sub Sector Livestock and Forestry Sector. While valuable under that sub-sector of the food crops and fisheries sub-sector. Competitive sectors namely food crops sub-sector, sub-sector plantations, livestock sub-sector and the results. The projected average growth of the agricultural sector in the next five years between the years 2013-2017 is 3.26% agricultural sector, sub-sector of food crops by 2.43%, 4.86% plantation sub-sector, sub-sector of livestock and the result is 3.21 %, -9.24% forestry sub-sector and fisheries sub-sector of 0.67%. Â  Â  Keywords: Contributions, Seed Sector, Changes In The Structure And Projections